Security of small network storage type NAS in the public sector - Salii, Vladyslav (Univerzita Pardubice, 2025)
This bachelor thesis focuses on the security aspects of small Network-Attached Storage (NAS) systems in the public sector. The thesis first defines basic concepts such as NAS components, architecture, common vulnerabilities, and cybersecurity measures. Subsequently, the thesis analyses potential threats and risks specific to public sector institutions using NAS systems. Based on selected case studies and supervisor's recommendations, the thesis proposes solutions to enhance the security and reliability of NAS in public administration.
Keywords: NAS; síťové úložiště; kybernetická bezpečnost; veřejný sektor; ochrana dat; zranitelnosti; šifrování; NAS; network storage; cybersecurity; public sector; data protection; vulnerabilities